Evolutionary trade‐off between male colouration and feather moult extent also indirectly determines female moult. (29th December 2021) - Kiat, Yosef; Sapir, Nir
Abstract: Males and females are often influenced by different selective forces, frequently resulting in diverging phenotypes, for example in colouration. Since an animal's colouration may strongly influence its fitness, causes and consequences of sexual dichromatism in birds could aid in understanding important factors affecting sexual and natural selection. Variation in plumage ornamentation may affect mate attraction or intraspecific antagonistic behaviour. In most passerines, body plumage colouration of juveniles is obtained through the process of feather moult. The number of moulted wing and tail feathers, which also influences the bird's appearance, may affect its fitness. Here, we show that body plumage colouration of male, but not female, passerines is correlated with the number of moulted wing and tail feathers in the early stage of the bird's life for both sexes. Thus, the extent of wing and tail moult in females is not modulated by the female's colouration and can prevent females from reaching their sex‐specific optima. This result could be explained by high intersexual genetic correlations, which might make it impossible for the sexes to reach their own trait fitness optima. Our findings may indicate that species‐specific, rather than sex‐specific, internal correlations shaped bird moult strategy, an important avian life‐history trait. Abstract : Body plumage colouration of juvenile passerines is obtained through the process of moult. Using a comparative approach, we show that body plumage colouration of male, but not female, passerines is correlated with the number of moulted wing and tail feathers in the early stage of the bird's life for both sexes. Yet, the extent of juvenile wing and tail moult in females is not associated with female colouration and this may prevent females from reaching their sex‐specific feather moult extent optima. These findings may indicate that species‐specific, rather than sex‐specific, internal correlations shape bird moult strategy, an important avian life‐history trait.